Improved high‐speed capillary electrophoresis system using a short capillary and picoliter‐scale translational spontaneous injection. Issue 16 (August 2014) - Zhang, Ting; Fu, Jinglin; Fang, Qun; Garcia, Carlos D.; Carrilho, Emanuel
<x xml:space="preserve">Abstract</x> Here, we describe an improved high‐speed CE (HSCE) system using a short capillary and translational spontaneous sample injection. Several important factors for consideration in system design as well as various factors influencing the performance of the HSCE system were investigated in detail. The performance of this HSCE system was demonstrated in electrophoretic separation of FITC‐labeled amino acids. Under optimized conditions, baseline separation of eight amino acids and FITC were achieved in 21 s with the plate heights ranging from 0.20 to 0.31 μm, corresponding to a separation rate up to 20 700 theoretical plates per second. The separation speed and efficiency of the optimized high‐speed CE system are comparable to or even better than those reported in microchip‐based CE systems.